DESIGN OF CUBIC Ni-BASED ALLOYS FOR USE AS COATING IN PETROCHEMICAL INDUSTRY – A FIRST PRINCIPLES APPROACH - Phasha, Maje; Mulaudzi, Marandela; Moller, Heinrich (The South African Journal of Industrial Engineering, 2022)
This work presents the structural stability and mechanical properties of ordered face-centred cubic (FCC) Ni-Cr binary and ternary alloys. The effects of alloying on these properties have been evaluated using the first principles density functional theory (DFT) within generalised gradient approximation (GGA). The calculated heats of formation show that the introduction of third elements (Al, Ti, Mo, Sn) improved the thermodynamic stability of the usually unstable L12 Ni3Cr phase. Unsurprisingly, ternary alloys that yielded higher mechanical properties were those alloyed with Al and Ti owing to their ability to form a very stable L12 phase with Ni. Therefore, the theoretical technique has been successfully employed to identify promising high-strength cubic Ni-based ternary intermetallic alloys that can be used as coatings.